The Effect of Perceived Organizational Support and Person-Job Fit on Performance in National Private Banks - Puti Harissa Pratidhina (Almana : Jurnal Manajemen dan Bisnis, 2026)
The relationship between employees and the banking industry has a significant impact on the bank's sustainability. Therefore, research is needed to explore the relationship between perceived organizational support and person-job fit on employee performance at a national private bank. In the banking industry, employee performance is strongly influenced by a supportive work environment that aligns with the individual's abilities and competencies. Perceived organizational support is a crucial factor in increasing employee loyalty and job satisfaction, which in turn positively impacts productivity. Meanwhile, individual-job fit plays a role in ensuring that employee skills and competencies align with job demands, thereby increasing work effectiveness. A correlational approach was used based on secondary data analysis from the bank in question, which included performance indicators, organizational support policies, and job fit. No direct employee surveys were conducted; Instead, the analysis focuses on the correlation between existing performance data and these organizational variables. The analysis revealed a positive and significant relationship between perceived organizational support and person-job fit on employee performance. These results suggest that organizational policies that address employee well-being and the alignment of employee competencies with assigned tasks play a significant role in increasing productivity.